THE CULT AND COMMEMORATION OF ST. VOSKEANS AND ST. SUKEASEANS IN THE LIGHT OF CAUCASIAN PARALLELS - Симонян, Лилит (History, Archeology and Ethnography of the Caucasus, 2021)
The obscure story about a group of early Christian saints of Alanian origin reports on the existence of the “grass-eaters” kind of Christianity in some regions of historical Armenia before the adoption of state Christianity. For the name of the group’s leader Sukias was Bahadras before his baptism, some parallels in the Armenian folk-lore and the Caucasian epic of Narts can proceed. The center of the cult of St. Sukiaseans was mountain Sukavet until the beginning of the 20th century. After its loss, however, the former inhabitants of Alashkert founded a chapel with vital worship and pilgrimage in the village of Nerkin Getashen, although the legendary story of the saints did not reach our times in memory of the people.